Newborn screening for SCID: lessons learned. Issue 6 (2nd June 2016) - Buelow, Becky J.; Verbsky, James W.; Routes, John M.
ABSTRACT: Introduction : Newborn screening (NBS) for Severe combined immunodeficiency (SCID)/severe T cell lymphopenia (sTCL) is being increasingly used worldwide. Areas covered : In this manuscript we will discuss the following: 1) The rationale for screening newborns for SCID/sTCL; 2) The scientific basis for the use of the T cell receptor excision circle (TREC) assay in screening newborns for SCID/sTCL; 3) The published outcomes of current NBS programs. Expert commentary : 4) Some of the ethical dilemmas that occur when screening newborns for SCID. Finally, we will discuss the future directions for expanding NBS to include other primary immunodeficiencies.